Climate Futures for Lizards and Snakes in Western North America May Result in New Species Management Issues - David S. Pilliod; Michelle I. Jeffries; Robert S. Arkle; Deanna H. Olson (Ecology and Evolution)
ABSTRACT We assessed changes in fundamental climate‐niche space for lizard and snake species in western North America under modeled climate scenarios to inform natural resource managers of possible shifts in species distributions. We generated eight distribution models for each of 130 snake and lizard species in western North America under six time‐by‐climate scenarios. We combined the highest‐performing models per species into a single ensemble model for each scenario. Maps were generated from the ensemble models to depict climate‐niche space for each species and scenario. Patterns of species richness based on climate suitability and niche shifts were calculated from the projections at the scale of the entire study area and individual states and provinces, from Canada to Mexico. Squamate species' climate‐niche space for the recent‐time climate scenario and published known ranges were highly correlated (r = 0.81). Overall, reptile climate‐niche space was projected to move northward in the future. Sixty‐eight percent of species were projected to expand their current climate‐niche space rather than to shift, contract, or remain stable. Only 8.5% of species were projected to lose climate‐niche space in the future, and these species primarily occurred in Mexico and the southwestern U.S. We found few species were projected to lose all suitable climate‐niche space at the state or province level, although species were often predicted to occupy novel areas, such as at higher elevations. Most squamate species were projected to increase their climate‐niche space in future climate scenarios. As climate niches move northward, species are predicted to cross administrative borders, resulting in novel conservation issues for local landowners and natural resource agencies. However, information on species dispersal abilities, landscape connectivity, biophysical tolerances, and habitat suitability is needed to contextualize predictions relative to realized future niche expansions.